A rare case scenario of transection of cervix during laparoscopic adenomyomectomy for a cervical fibroid: a nightmare of gynecologist - Dhandapani, Kalyani Sai; Kalidoss, Madhubala (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
We are reporting a case of complete cervical transection during adenomyomectomy, a disconnection between uterus and cervix which is a rare complication of myomectomy procedure. A 32-year-old presented with secondary subfertility with heavy menstrual bleeding. Ultrasound showed a large cervical adenomyoma of posterior lip for which adenomyomectomy was performed. During enucleation of the myoma, cervical transection encountered. Successful reconstruction of the uterus to cervix done following which MRI performed six months later showed complete reanastomosis of uterus to cervix followed by regular establishment of periodic menstruation.